Information Technology as a catalyst for the professionalisation of academic administrators: A case study of a health sciences faculty - Simpson, M.; Shaw, C. (South African Journal of Higher Education, 2023)
As academic administrators become a key staffing component of efficiently run universities, their role as knowledge workers is being reframed. This is especially evident as universities increasingly rely on information technologies and student information systems to process vast amounts of student data in the pursuit of improving student success and assisting senior management with future planning. In this study, a qualitative research approach was employed to explore the enabling factors that contributed to academic administrators becoming central to various data quality management processes. Twenty-six (26) participants were purposively selected to participate in this study. Data collection strategies included the use of semi-structured interviews, focus groups, observations and documentary sources. The findings demonstrate the interrelationship between the professionalisation of academic administrators and enhanced data quality management processes. The results reassert the argument for reconceptualising the role of academic administrators as knowledge workers. This position has implications for how such staff are perceived within the organisational structure of the university and the types of staff development and training required.